(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
This study aims to identify and describe community empowerment through the utilization of Village Fund Allocation (ADD) in Walewangko Village, West Langowan Subdistrict, Minahasa District. The research method used in this research is qualitative method. The main instrument in this study is the researchers themselves; while the data collection techniques used are Interview, Observation, Documentation. The results showed that community empowerment through the utilization of Village Fund Allocation can improve the empowerment of the small or less capable communities. community empowerment activities through the utilization of Village Fund Allocation in the Village Walewangko still limited or still reach a small part of society Keywords: Empowerment, Allocation of Village Funds